Positive electrode active material for secondary battery and secondary battery

By using lithium transition metal oxide as the positive electrode active substance in aqueous lithium secondary batteries and adding specific oxides to its surface, combined with an optimized aqueous electrolyte formula, the reduction in capacity and battery deterioration during charging and storage is solved, and the problem of improved capacity is improved. The durability and safety of the battery.

CN112703620BActive Publication Date: 2024-12-13PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN201980058930.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-27
Filing Date
2019-07-26
Publication Date
2024-12-13
Estimated Expiration
2039-07-26

AI Technical Summary

Technical Problem

The existing water-based lithium secondary batteries have a reduced capacity and battery deterioration problems during charging and storage, especially when the electrolytic reaction of water at high voltages, resulting in insufficient battery durability.

Method used

A specific positive electrode active material LixM1-yLyO2 is used to contain lithium transition metal oxides, and B, Si, P, Ti, V, Mn, Al, Mg, Ca, Zr, W, Nb, Ta, In are added to its surface portion. Oxides of elements such as Mo and Sn, combined with optimized aqueous electrolyte formulations, including high fluorine alkaline earth metal salts and fluorophosphate, inhibit the electrolysis and oxidative decomposition of water.

Benefits of technology

It effectively suppresses the reduction in capacity during charging and storage capacity and battery deterioration, improves the durability and safety of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112703620B_ABST
    Figure CN112703620B_ABST
Patent Text Reader

Abstract

The positive electrode active material is the general formula Li x M 1‑y L y O2 (wherein, 0.9≤x≤1.1, 0≤y<0.6; element M is at least one selected from the group consisting of Ni and Co; element L is at least one selected from the group consisting of alkaline earth elements, transition metal elements other than Ni and Co, rare earth elements, IIIb group elements and IVb group elements), and the surface layer of the positive electrode active material has an oxide of at least one element Me selected from the group consisting of B, Si, P, Ti, V, Mn, Al, Mg, Ca, Zr, W, Nb, Ta, In, Mo and Sn.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a positive electrode active material for a secondary battery and a secondary battery. Background Art

[0002] Aqueous lithium secondary batteries using aqueous solutions as electrolytes are known. Aqueous lithium secondary batteries are required to be used within a potential range where no electrolysis reaction of water occurs. It is necessary to use an active material that is stable in an aqueous solution and can reversibly absorb and detach a large amount of lithium within a potential range where oxygen and hydrogen are not produced by the electrolysis of water. In other words, it is necessary to use an active material that can exert a large capacity within a specific potential range. In addition, as an electrolyte, it is desirable to use a neutral to alkaline electrolyte. When a neutral, i.e., pH=7, electrolyte is used, the decomposition voltage of water is as follows: hydrogen evolution potential is 2.62V, and oxygen evolution potential is 3.85V. In addition, when a strongly alkaline, i.e., pH=14, electrolyte is used, the decomposition voltage of water is as follows: hydrogen evolution potential is 2.21V, and oxygen evolution potential is 3.44V.

[0003] Therefore, as a positive electrode active material, a material that can absorb more Li up to a minimum of 3.85 V (pH=7) is desired, and as a negative electrode active material, a material that can absorb more Li up to 2.21 V (pH=14) is desired.

[0004] Patent Document 1 describes a positive electrode active material having the general formula Li s Ni x Co y Mn z M t A layered structure compound represented by O2 (0.9≤s≤1.2, 0.25≤x≤0.4, 0.25≤y≤0.4, 0.25≤z≤0.4, 0≤t≤0.25; M is one or more selected from Mg, Al, Fe, Ti, Ga, Cu, V and Nb) is used as the main component.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 4581524 Summary of the invention

[0008] For secondary batteries using aqueous electrolytes, there is a demand for a technology that can expand the potential region where electrolysis does not occur and improve durability, that is, suppress capacity reduction and battery degradation during charged storage.

[0009] The object of the present application is to provide a positive electrode active material for a secondary battery using an aqueous electrolyte and a secondary battery using an aqueous electrolyte, wherein a decrease in capacity and battery degradation during charged storage are suppressed, and a secondary battery is provided.

[0010] The positive electrode active material according to one embodiment of the present application is a positive electrode active material for a secondary battery having an electrolyte solution prepared by dissolving a lithium salt in water, and comprises a general formula Li x M 1-y L y The positive electrode active material is a composite oxide having an oxide of at least one element Me selected from the group consisting of B, Si, P, Ti, V, Mn, Al, Mg, Ca, Zr, W, Nb, Ta, In, Mo and Sn on the surface of the lithium transition metal oxide.

[0011] According to the present application, it is possible to suppress a decrease in capacity and battery degradation during charged storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a diagram for explaining the function of the implementation method.

[0013] Figure 2 Schematic diagram of a positive electrode active material according to an embodiment. DETAILED DESCRIPTION

[0014] As a result of intensive studies, the present inventors have found that battery degradation during charged storage can be suppressed by using a specific material as a positive electrode active material in an electrolyte solution containing water as a solvent and a lithium salt as an electrolyte salt.

[0015] Hereinafter, an embodiment of a positive electrode active material and a secondary battery according to one embodiment of the present application will be described. However, the embodiment described below is an example, and the present application is not limited thereto.

[0016] [Aqueous electrolyte]

[0017] The aqueous electrolyte described in this embodiment contains at least water and a lithium salt. It should be noted that when using an electrolyte containing water as a solvent, since water theoretically decomposes at a voltage of 1.23V, it is also desired to develop a secondary battery that can work stably without decomposing water even when a higher voltage is applied.

[0018] (Solvent)

[0019] The aqueous electrolyte contains water as the main solvent. Here, containing water as the main solvent means that the content of water is 50% or more by volume relative to the total amount of solvent contained in the electrolyte. The content of water contained in the electrolyte is preferably 90% or more by volume relative to the total amount of solvent. The solvent contained in the electrolyte can be a mixed solvent containing water and a non-aqueous solvent. Examples of the non-aqueous solvent include alcohols such as methanol; carbonates such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, and propylene carbonate; acetone; acetonitrile; and non-protonic polar solvents such as dimethyl sulfoxide.

[0020] The aqueous electrolyte contains non-flammable water as the main solvent, so the safety of the secondary battery using the aqueous electrolyte can be improved. From this viewpoint, the content of water is preferably 8% by mass or more, more preferably 10% by mass or more relative to the total amount of the electrolyte. In addition, the content of water is preferably 50% by mass or less, more preferably 20% by mass or less relative to the total amount of the electrolyte.

[0021] (Lithium Salt)

[0022] The lithium salt contained in the aqueous electrolyte can be used as long as it is a compound that can be dissolved in a solvent containing water and dissociated so that lithium ions are present in the aqueous electrolyte. The lithium salt preferably does not cause deterioration of battery characteristics due to its reaction with the materials constituting the positive electrode and the negative electrode. Examples of such lithium salts include salts formed with inorganic acids such as perchloric acid, sulfuric acid and nitric acid; salts formed with halide ions such as chloride ions and bromide ions; and salts formed with organic anions containing carbon atoms in the structure.

[0023] Examples of the organic anions constituting the lithium salt include anions represented by the following general formulae (i) to (iii).

[0024] (R 1 SO2)(R 2 SO2)N - (i)

[0025] (R 1 , R 2 R is independently selected from a halogen atom, an alkyl group or a halogen-substituted alkyl group. 1 and R 2 They are optionally bonded to each other to form a ring.)

[0026] R 3 SO3 - (ii)

[0027] (R 3 is selected from a halogen atom, an alkyl group or a halogen-substituted alkyl group. )

[0028] R4 CO2 - (iii)

[0029] (R 4 is selected from alkyl or halogen-substituted alkyl. )

[0030] In the above general formulae (i) to (iii), the number of carbon atoms in the alkyl group or the halogen-substituted alkyl group is preferably 1 to 6, more preferably 1 to 3, and even more preferably 1 to 2. The halogen in the halogen-substituted alkyl group is preferably fluorine. The number of halogen substitutions in the halogen-substituted alkyl group is less than the number of hydrogen atoms in the original alkyl group. The halogen atom in the above general formulae (i) to (ii) is preferably a fluorine atom.

[0031] R 1 ~R 4 are, for example, saturated alkyl or saturated halogen-substituted alkyl and R 1 ~R 2 When they are not bonded to each other to form a ring, they may be a group represented by the following general formula (iv).

[0032] C n H a F b Cl c Br d I e (iv)

[0033] (n is an integer greater than or equal to 1, a, b, c, d, and e are integers greater than or equal to 0, and 2n+1=a+b+c+d+e is satisfied.)

[0034] In the above general formula (iv), from the viewpoint of oxidation resistance, a is preferably smaller, more preferably a=0, and most preferably 2n+1=b.

[0035] Specific examples of the organic anion represented by the general formula (i) include bis(fluorosulfonyl)imide (FSI; [N(FSO2)2] - ), bis(trifluoromethanesulfonyl)imide (TFSI; [N(CF3SO2)2] - ), bis(perfluoroethanesulfonyl)imide (BETI; [N(C2F5SO2)2] - ), (perfluoroethanesulfonyl)(trifluoromethanesulfonyl)imide ([N(C2F5SO2)(CF3SO2)] - ) etc. In addition, as R 1 ~R 2 Specific examples of organic anions that are bonded to each other to form a ring include cTFSI; ([N(CF2SO2)2] -) etc. Specific examples of organic anions represented by the general formula (ii) include FSO3 - CF3SO3 - 、C2F5SO3 - As specific examples of the organic anion represented by the general formula (iii), for example, CF3CO2 - 、C2F5CO2 - wait.

[0036] Examples of organic anions other than those of the general formula (i) include bis(1,2-benzenediol (2-)-O,O')borate, bis(2,3-naphthalenediol (2-)-O,O')borate, bis(2,2'-biphenylenediol (2-)-O,O')borate, and bis(5-fluoro-2-ol-1-benzenesulfonic acid-O,O')borate.

[0037] As the anion constituting the lithium salt, the imide anion is preferably used. As suitable specific examples of the imide anion, in addition to the imide anion exemplified as the organic anion represented by the general formula (i), (fluorosulfonyl) (trifluoromethanesulfonyl) imide (FTI; [N(FSO2)(CF3SO2)] - )wait.

[0038] Specific examples of lithium salts having lithium ions and imide anions include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(perfluoroethanesulfonyl)imide (LiBETI), lithium (perfluoroethanesulfonyl)(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide (LiFSI), and lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide (LiFTI).

[0039] Specific examples of other lithium salts include CF3SO3Li, C2F5SO3Li, CF3CO2Li, C2F5CO2Li, bis(1,2-benzenediol (2-)-O,O') lithium borate, bis(2,3-naphthalenediol (2-)-O,O') lithium borate, bis(2,2'-biphenylenediol (2-)-O,O') lithium borate, bis(5-fluoro-2-ol-1-benzenesulfonic acid-O,O') lithium borate, lithium perchlorate (LiClO4), lithium chloride (LiCl), lithium bromide (LiBr), lithium hydroxide (LiOH), lithium nitrate (LiNO3), lithium sulfate (Li2SO4), lithium sulfide (Li2S), lithium hydroxide (LiOH), etc.

[0040] In the aqueous electrolyte according to this embodiment, the molar ratio of water to the lithium salt is preferably 15:1 or less, more preferably 4:1 or less. This is because when the molar ratio of water to the lithium salt is within these ranges, the potential window of the aqueous electrolyte expands, and the applied voltage can be further increased for the secondary battery. From the viewpoint of the safety of the secondary battery, the molar ratio of water to the lithium salt is preferably 1.5:1 or more.

[0041] (Additive)

[0042] The aqueous electrolyte according to this embodiment may further contain additives and other electrolytes known in the art. As the other electrolyte, a solid electrolyte having lithium ion conductivity may be further contained.

[0043] Examples of the additive include, for example, fluorophosphate, carboxylic anhydride, alkaline earth metal salt, sulfur compound, acid and base, etc. The aqueous electrolyte preferably further contains at least one of fluorophosphate, carboxylic anhydride, alkaline earth metal salt and sulfur compound. The content of these additives is 0.1% by mass or more and 5.0% by mass or less with respect to the total amount of the aqueous electrolyte, for example.

[0044] Examples of the fluorophosphate that can be added to the aqueous electrolyte include lithium fluorophosphate salts represented by the general formula LixPFyOz (1 ≤ x < 3, 0 < y ≤ 2, 2 ≤ z < 4). By making the aqueous electrolyte contain fluorophosphate, the electrolysis of water can be suppressed. Specific examples of the lithium fluorophosphate salt include, for example, lithium difluorophosphate (LiPF2O2), lithium monofluorophosphate (Li2PFO3), and LiPF2O2 is preferred. It should be noted that the fluorophosphate represented by the general formula LixPFyOz may be a mixture of multiple ones selected from LiPF2O2, Li2PFO3, and Li3PO4. In this case, x, y, and z may be values other than integers. The content of the fluorophosphate is sufficient as long as it is 0.1% by mass or more with respect to the total amount of the aqueous electrolyte, for example, and preferably 0.3% by mass or more. In addition, the content of the lithium fluorophosphate salt is sufficient as long as it is 3.0% by mass or less with respect to the total amount of the aqueous electrolyte, for example, and preferably 2.0% by mass or less.

[0045] The alkaline earth metal salt that can be added to the aqueous electrolyte is a salt having an ion of an alkaline earth metal (Group 2 element) and an anion such as an organic anion. Examples of the alkaline earth metal include, for example, beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), and magnesium and calcium are preferred.

[0046] As the organic anion constituting the alkaline earth metal salt, for example, the organic anions represented by the general formulae (i) to (iii) described as the organic anions constituting the above-mentioned lithium salt can be listed. However, the anion constituting the alkaline earth metal salt may be an organic anion other than the organic anions represented by the general formulae (i) to (iii), or may be an inorganic anion.

[0047] The dissociation constant of the alkaline earth metal salt in the aqueous electrolyte is preferably large. For example, suitable examples include alkaline earth metal salts of perfluoroalkanesulfonic acid imides such as Ca[N(CF3SO3)2]2(CaTFSI), Ca[N(CF3CF3SO2)2]2(CaBETI), Mg[N(CF3SO3)2]2(MgTFSI), and Mg[N(CF3CF3SO2)2]2(MgBETI); alkaline earth metal salts of trifluoromethanesulfonic acid such as Ca(CF3SO3)2 and Mg(CF3SO3)2; alkaline earth metal salts of perchloric acid such as Ca[ClO4]2 and Mg[ClO4]2; and tetrafluoroborates such as Ca[BF4]2 and Mg[BF4]2. Among these, alkaline earth metal salts of perfluoroalkanesulfonic acid imides are more preferred from the viewpoint of plasticizing effect, and CaTFSI and CaBETI are particularly preferred. In addition, as alkaline earth metal salt, it is also preferred to have an alkaline earth metal salt with the same anion as the Li salt contained in the electrolyte. The alkaline earth metal salt can be used alone or in combination with two or more. From the viewpoint of the potential window expanding to the low potential side, the content of the alkaline earth metal salt is, for example, 0.5 mass % or more and 3 mass % or less relative to the total amount of the aqueous electrolyte, preferably 1.0 mass % or more and 2 mass % or less.

[0048] The carboxylic anhydride that can be added to the aqueous electrolyte includes cyclic carboxylic anhydride and chain carboxylic anhydride. As cyclic carboxylic anhydride, for example, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, diglycolic anhydride, cyclohexane dicarboxylic anhydride, cyclopentane tetracarboxylic anhydride, phenyl succinic anhydride, etc. can be listed. Chain carboxylic anhydride is an anhydride of two identical or different carboxylic acids selected from carboxylic acids having 1 to 12 carbon atoms such as acetic acid, propionic acid, butyric acid, isobutyric acid, etc. As a specific example thereof, acetic anhydride, propionic anhydride, etc. can be listed. When added to the aqueous electrolyte, the carboxylic anhydride can be used alone or in combination of two or more. The content of the carboxylic anhydride is, for example, 0.1% by mass or more and 5.0% by mass or less relative to the total amount of the aqueous electrolyte, preferably 0.3% by mass or more and 2.0% by mass or less.

[0049] As sulfur compounds that can be added to the aqueous electrolyte, there can be listed, for example, organic compounds containing sulfur atoms in the molecule, and the compound does not contain the above-mentioned lithium salts, carboxylic acids and alkaline earth metal salts. By including the sulfur compound in the aqueous electrolyte, it is possible to compensate for the coating containing components derived from the reduction reaction of anions represented by general formulas (i) to (iii) such as TFSI and BETI, and it is possible to efficiently block the parasitic hydrogen evolution in the negative electrode. As specific examples of sulfur compounds, there can be listed, for example, cyclic sulfur compounds such as ethylene sulfite, 1,3-propane sultone, 1,4-butane sultone, cyclopentane sulfone, cyclobutene sulfone; sulfonic acid esters such as methyl methanesulfonate and busulfan; sulfones such as dimethyl sulfone, diphenyl sulfone, and methyl phenyl sulfone; sulfides or disulfides such as dibutyl disulfide, dicyclohexyl disulfide, and tetramethylthiuram monosulfide; sulfonamides such as N,N-dimethylmethanesulfonamide and N,N-diethylmethanesulfonamide, etc. Among these sulfur compounds, ethylene sulfite, 1,3-propane sultone, 1,4-butane sultone, cyclopentane sulfone, etc. are preferred, and ethylene sulfite is particularly preferred. When added to the aqueous electrolyte, the sulfur compound can be used alone or in combination of two or more. The content of the sulfur compound can be, for example, 0.1% by mass or more and 5.0% by mass or less relative to the total amount of the aqueous electrolyte, preferably 0.3% by mass or more and 2.0% by mass or less.

[0050] The method for preparing the aqueous electrolyte according to the present embodiment is not particularly limited, and the aqueous electrolyte may be prepared by, for example, appropriately mixing water, a lithium salt, and the above-mentioned additives when adding.

[0051] The pH of the aqueous electrolyte is not particularly limited, for example, as long as it is greater than 3 and less than 14, preferably greater than 10. This is because: when the pH of the aqueous electrolyte is within these ranges, the stability of the positive electrode active material in the positive electrode and the negative electrode active material in the negative electrode in the aqueous solution can be improved, and the absorption and desorption reactions of lithium ions in the positive electrode active material and the negative electrode active material can become smoother.

[0052] [Secondary battery]

[0053] Hereinafter, a secondary battery described in an example of an embodiment of the present application will be described. A secondary battery as an example of an embodiment comprises the above-mentioned aqueous electrolyte, a positive electrode and a negative electrode. The secondary battery has a structure in which, for example, an electrode body comprising a positive electrode, a negative electrode and a separator and an aqueous electrolyte are contained in a battery case. As the electrode body, for example, a wound electrode body in which a positive electrode and a negative electrode are wound with a separator therebetween, a stacked electrode body in which a positive electrode and a negative electrode are stacked with a separator therebetween, etc. can be cited, and the form of the electrode body is not limited thereto.

[0054] Battery cases for housing the electrode bodies and aqueous electrolytes include cylindrical, square, coin-shaped, button-shaped, and other metal or resin cases; and resin cases formed by laminating metal foils with resin sheets (laminated batteries).

[0055] The secondary battery described in this embodiment can be manufactured using a known method, for example, by housing a wound or stacked electrode body in a battery case body, injecting an aqueous electrolyte, and then sealing the opening of the battery case body with a gasket and a sealing body.

[0056] [positive electrode]

[0057] The positive electrode constituting the secondary battery described in this embodiment is composed of, for example, a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector. The positive electrode active material layer can be formed on one surface of the positive electrode collector or on both surfaces. The positive electrode active material layer includes, for example, a positive electrode active material, a binding material, a conductive material, etc.

[0058] As the positive electrode current collector, a foil of a metal that is stable within the potential range of the positive electrode and a thin film of the metal disposed on the surface layer can be used. As the positive electrode current collector, a porous body such as a mesh body, a punched sheet, and a metal plate net of the metal can be used. As the material of the positive electrode current collector, stainless steel, aluminum, aluminum alloy, titanium, etc. can be used. From the viewpoints of current collection, mechanical strength, etc., the thickness of the positive electrode current collector is preferably, for example, 3 μm or more and 50 μm or less.

[0059] The positive electrode can be obtained by, for example, coating a positive electrode composite material slurry containing a positive electrode active material, a conductive material, a binding material, etc. on a positive electrode collector and drying it, thereby forming a positive electrode active material layer on the positive electrode collector, and rolling the positive electrode active material layer. As a dispersion medium used in the positive electrode composite material slurry, for example, water, ethanol and other alcohols, ethers such as tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), etc. can be used. The thickness of the positive electrode active material layer is not particularly limited, for example, 10 μm or more and 100 μm or less.

[0060] The positive electrode active material includes a lithium transition metal oxide containing lithium (Li) and transition metal elements such as cobalt (Co), manganese (Mn) and nickel (Ni). As a specific example of the lithium transition metal oxide, Li x M 1-y L yO2 represents. With respect to x, it is preferably 0.9≤x≤1.1, and more preferably 0.95≤x≤1.02. With respect to y, from the viewpoint of crystal structure stability, it is preferably 0≤y<0.6. The element M is at least one selected from the group consisting of nickel (Ni) and cobalt (Co). In addition, the element L is at least one selected from the group consisting of alkaline earth elements, transition metal elements other than Ni and Co, rare earth elements, IIIb group elements, and IVb group elements.

[0061] From the viewpoint of increasing the capacity, the lithium transition metal oxide preferably contains 40 mol % or more, more preferably 90 mol % or more, of Ni based on the total amount of transition metals excluding lithium.

[0062] In addition, the positive electrode active material is a composite oxide having an oxide of at least one element Me selected from the group consisting of boron (B), silicon (Si), phosphorus (P), titanium (Ti), vanadium (V), manganese (Mn), aluminum (Al), magnesium (Mg), calcium (Ca), zirconium (Zr), tungsten (W), niobium (Nb), tantalum (Ta), indium (In), molybdenum (Mo) and tin (Sn) in the surface layer of the lithium transition metal oxide.

[0063] Figure 1 A schematic illustration of the positive electrode active material 10 described in the present embodiment is shown. In a secondary battery using an aqueous electrolyte, the capacity is reduced by self-discharge caused by embedding protons from the electrolyte into the positive electrode active material 10. In particular, the capacity can be reduced when a positive electrode active material with a high Ni ratio is used. In addition, the capacity can be reduced by exchanging protons with Li ions (proton exchange). Furthermore, the capacity can also be reduced by oxidative decomposition of water and the accompanying acidification of the electrolyte. In contrast, by the presence of an oxide such as W on the surface of the positive electrode active material, the oxide is used to suppress proton embedding, proton exchange and oxidative decomposition of water, thereby suppressing capacity reduction and voltage reduction.

[0064] Figure 1 A cross-sectional SEM image 12 of the surface of the positive electrode active material 10 based on a scanning electron microscope (SEM) is also shown. It should be noted that the cross-sectional SEM image 12 can be obtained by embedding the positive electrode in a resin, making a cross section of the positive electrode by cross-sectional polishing (CP) processing, and photographing the cross section by SEM. It can be seen from the cross-sectional SEM image 12 that: oxides exist in the surface of the positive electrode active material. When the positive electrode active material 10 contains primary particles and secondary particles formed by aggregation of primary particles, the oxide is preferably present in the surface of the secondary particles, and also in the surface of the primary particles. By having oxides not only in the surface of the secondary particles, but also in the surface of the primary particles, proton embedding, proton exchange, etc. can be reliably suppressed.

[0065] The element Me present in the surface layer of the lithium transition metal oxide particles is preferably precipitated, attached, or supported on the surface of the lithium transition metal oxide in the form of an oxide.

[0066] The element L solid-dissolved in the lithium transition metal oxide and the element Me present in the surface layer of the lithium transition metal oxide particles may contain the same kind of elements or may not contain them. Even if the element Me and the element L contain the same kind of elements, they are clearly distinguished due to differences in crystal structure, etc. The element Me is not solid-dissolved in the lithium transition metal oxide, but mainly constitutes an oxide having a crystal structure different from that of the lithium transition metal oxide in the surface layer of the lithium transition metal oxide particles. The element Me and the element L can be distinguished by various analysis methods headed by element mapping based on EPMA (electron probe micro-analyzer: Electron Probe Micro-Analysis), analysis of chemical bond states based on XPS (X-ray photoelectron spectroscopy: X-ray Photoelectron Spectroscopy), and SIMS (Secondary Ionization Mass Spectroscopy).

[0067] The amount of element Me contained in the active material particles is preferably less than 2 mol% relative to the lithium transition metal oxide. If the amount of element Me exceeds 2 mol%, a resistance layer is formed on the surface of the lithium transition metal oxide particles, the overvoltage becomes larger, and therefore, the cycle characteristics begin to decrease. On the other hand, when the amount of element Me is less than 0.1 mol%, the exposed portion of the lithium transition metal oxide becomes more, and therefore, the effect of suppressing the decrease in capacity during charging and storage is sometimes not obtained. The average particle size (D50) of the composite oxide particles is preferably, for example, greater than 2 μm and less than 20 μm. When the average particle size (D50) is less than 2 μm and exceeds 20 μm, the packing density in the positive electrode active material layer is sometimes reduced and the capacity is reduced compared to the case where the above range is satisfied. The average particle size (D50) of the positive electrode active material can be measured by using, for example, MT3000II manufactured by MICROTRAC BELL and by laser diffraction.

[0068] An example of a method for producing composite oxide particles will be described.

[0069] First, an aqueous solution of a raw material of element Me is mixed and dissolved in a precursor (hydroxide) to form a slurry, and the pH is adjusted to precipitate a compound containing Me. Thereafter, a precursor loaded with element Me is prepared by heat treatment at 500 to 750° C. It should be noted that as a raw material of element Me, any water-soluble salt may be used, including nitrates, sulfates, acetates, carbonates, oxalates, silicates, phosphates, alkali metal salts, ammonium salts, etc., and ammonium salts are particularly useful.

[0070] Thereafter, a Li source is mixed into the precursor, and the resulting mixture is pre-calcined in an oxygen gas flow (oxygen concentration: 100 volume %) at, for example, 500° C. for 4 hours, then calcined at 730° C. for 24 hours, cooled, and then crushed to produce a positive electrode active material.

[0071] Thereby, a positive electrode active material in which an oxide of the element Me exists on both the primary particle surface and the secondary particle surface can be synthesized.

[0072] Figure 2 The schematic diagram of the positive electrode active material in this embodiment includes primary particles 14 and secondary particles 16 formed by aggregation of the primary particles 14 , and oxides 18 of element Me (eg, W) exist on the surfaces of the primary particles 14 and the surface layers of the secondary particles 16 .

[0073] It should be noted that in this method, the raw material of the element Me is mixed with the precursor before the calcination step, but there is also a method in which the raw material of the element Me is mixed after the precursor is calcined. However, in this case, the oxide of the element Me exists only on the surface of the secondary particles.

[0074] Examples of the conductive material contained in the positive electrode active material layer include carbon black, acetylene black, Ketjen black, graphite and other carbon powders, etc. These may be used alone or in combination of two or more.

[0075] As the binding material contained in the positive electrode active material layer, for example, fluorine-based polymers, rubber-based polymers, etc. can be listed. As fluorine-based polymers, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF) or their modified bodies can be listed, and as rubber-based polymers, for example, ethylene-propylene-isoprene copolymers, ethylene-propylene-butadiene copolymers, etc. can be listed. They can be a single one, or two or more can be used in combination.

[0076] The positive electrode of the present embodiment can be obtained by, for example, applying a positive electrode composite material slurry containing a positive electrode active material, a conductive material, a binder, etc., on a positive electrode current collector, drying the slurry to form a positive electrode active material layer, and rolling the positive electrode composite material layer.

[0077] [negative electrode]

[0078] The negative electrode constituting the secondary battery described in this embodiment is composed of, for example, a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector. The negative electrode active material layer may be formed on one surface of the negative electrode current collector or on both surfaces. The negative electrode active material layer includes, for example, a negative electrode active material, a binding material, and the like.

[0079] As the negative electrode current collector, a foil of a metal that is stable within the potential range of the negative electrode, and a thin film of the metal disposed on the surface layer, etc. can be used. As the negative electrode current collector, a porous body such as a mesh body, a punched sheet, and a metal plate net of the metal can be used. As the material of the negative electrode current collector, copper, copper alloy, aluminum, aluminum alloy, stainless steel, nickel, etc. can be used. From the viewpoints of current collection, mechanical strength, etc., the thickness of the negative electrode current collector is preferably, for example, 3 μm or more and 50 μm or less.

[0080] The negative electrode can be prepared by, for example, coating a negative electrode composite material slurry containing a negative electrode active material, a binding material and a dispersion medium on a negative electrode collector and drying the coating film, and then rolling to form a negative electrode active material layer on one or both sides of the negative electrode collector. The negative electrode active material layer may contain any component such as a conductive agent as needed. The thickness of the negative electrode active material layer is not particularly limited, for example, 10 μm or more and 100 μm or less.

[0081] The negative electrode active material is not particularly limited as long as it is a material that can absorb / release lithium ions. The material constituting the negative electrode active material may be a non-carbon material, a carbon material, or a combination thereof. Examples of non-carbon materials include lithium metal, alloys containing lithium elements, and metal compounds such as metal oxides, metal sulfides, and metal nitrides containing lithium. Examples of alloys containing lithium elements include lithium aluminum alloys, lithium tin alloys, lithium lead alloys, and lithium silicon alloys. Examples of metal oxides containing lithium include metal oxides containing lithium and containing titanium, tantalum, or niobium, preferably lithium titanate (Li4Ti5O 12 wait).

[0082] As carbon materials used as negative electrode active materials, for example, graphite and hard carbon can be listed. Among them, graphite is preferred due to its high capacity and small irreversible capacity. Graphite is a general term for carbon materials with a graphite structure, including natural graphite, artificial graphite, expanded graphite, graphitized mesophase carbon particles, etc. When graphite is used as a negative electrode active material, in order to reduce the activity of reduction and decomposition of aqueous electrolytes, it is preferred to cover the surface of the negative electrode active material layer with a coating. These negative electrode active materials can be used alone or in combination of two or more.

[0083] As the binding material contained in the negative electrode active material layer, for example, fluorine-based polymers, rubber-based polymers, etc. can be used in the same manner as in the case of the positive electrode. In addition, styrene-butadiene copolymer (SBR) or its modified body can also be used. The content of the binding material contained in the negative electrode active material layer is preferably 0.1% by mass or more and 20% by mass or less relative to the total amount of the negative electrode active material, more preferably 1% by mass or more and 5% by mass or less. As the thickener contained in the negative electrode active material layer, for example, carboxymethyl cellulose (CMC), polyethylene oxide (PEO), etc. can be listed. They can be a single kind, or two or more kinds can be used in combination.

[0084] [Separator]

[0085] As a separator, there is no particular limitation as long as it has the function of passing lithium ions and electrically separating the positive electrode from the negative electrode, and for example, a porous sheet composed of a resin, an inorganic material, etc. can be used. Specific examples of porous sheets include microporous films, woven fabrics, non-woven fabrics, etc. As resin materials constituting the separator, olefin resins such as polyethylene and polypropylene; polyamide, polyamide-imide, cellulose, etc. can be listed. As inorganic materials constituting the separator, glasses and ceramics such as borosilicate glass, silica, alumina, and titanium dioxide can be listed. The separator can be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. In addition, it can be a multilayer separator comprising a polyethylene layer and a polypropylene layer, and a separator coated with a material such as an aromatic polyamide resin, ceramic, etc. on the surface of the separator can also be used.

[0086] It should be noted that, in the above embodiment, a secondary battery having an aqueous electrolyte is described, but the aqueous electrolyte described in one example of this embodiment can be used in a storage device other than a secondary battery, and can be used in, for example, a capacitor. In this case, the capacitor has, for example, an aqueous electrolyte described in one example of this embodiment and two electrodes. The electrode material constituting the electrode can be any material that can be used in a capacitor and can absorb and release lithium ions, and materials such as graphite-containing materials such as natural graphite or artificial graphite, and materials such as lithium titanate can be listed.

[0087] Example

[0088] Hereinafter, examples and comparative examples of the present application will be described in detail, but the present application is not limited to the following examples.

[0089] (Example 1)

[0090] A secondary battery was manufactured according to the following steps.

[0091] [Production of positive electrode]

[0092] In the lithium transition metal oxide (LiNi) containing Li, Ni, Co and Al as the positive electrode active material 0.82 Co 0.15 Al 0.03 O2(NCA)) was synthesized by coprecipitating the precursor hydroxide [(Ni 0.82 Co 0.15 Al 0.03 The steps of mixing )(OH)2] with an aqueous solution of ammonium metatungstate of a specified concentration to form a suspension, adding dilute sulfuric acid while stirring to make the pH reach 8.5, washing with water, and drying to obtain a precursor loaded with a W compound; and mixing the precursor with LiOH in a specified amount ratio, calcining at 750°C for 10 hours in an oxygen gas flow atmosphere to produce a composite oxide covered with W oxide on the surface. It should be noted that the amount of W oxide is adjusted to 0.15 mol% relative to the total amount of Ni, Co, and Al.

[0093] It was confirmed by SEM observation that the composite oxide included primary particles and secondary particles formed by aggregation of the primary particles, and that the W oxide existed on the surfaces of the primary particles and on the surface layer of the secondary particles.

[0094] In the composite oxide, acetylene black (AB) as a conductive material and polyvinylidene fluoride (PVdF) as a binder are mixed in a mass ratio of NCA:AB:PVdF=100:1:0.9, and then an appropriate amount of N-methyl-2-pyrrolidone (NMP) is added and stirred to prepare a positive electrode slurry. Then, the obtained positive electrode slurry is applied to one side of an aluminum foil (positive electrode collector), dried, and the coating of the positive electrode composite material is rolled using a roller to prepare the positive electrode of Example 1.

[0095] [Production of negative electrode]

[0096] Graphite as a negative electrode active material, styrene-butadiene copolymer (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener were mixed in a mass ratio of 100:1:1, and water was added to prepare a negative electrode composite material slurry. Next, the negative electrode composite material slurry was applied to both sides of a negative electrode collector formed of copper foil, dried, and then rolled using a calendering roller, thereby producing a negative electrode having a negative electrode active material layer formed on both sides of the negative electrode collector.

[0097] [Preparation of aqueous electrolyte]

[0098] LiN(SO2CF3)2, LiN(SO2C2F5)2, LiOH·H2O and water (ultrapure water) were mixed in a molar ratio of 0.7:0.3:0.034:1.923.

[0099] [Manufacturing of Secondary Batteries]

[0100] The positive electrode and the negative electrode were wound with a separator interposed therebetween to produce an electrode body, which was housed in a bottomed cylindrical battery case together with the aqueous electrolyte, and the opening of the battery case was sealed with a gasket and a sealing body.

[0101] (Comparative Example 1)

[0102] In the preparation process of the positive electrode active material, the positive electrode was prepared by the same method as in Example 1 except that the step of loading the W compound on the precursor was omitted. A secondary battery was prepared using the prepared positive electrode and evaluated in the same manner as in Example 1. That is, in Comparative Example 1, the lithium transition metal oxide (LiNi 0.82 Co 0.15 Al 0.03 O2(NCA)) was used as the positive electrode.

[0103] [Evaluation of Stability during Charge Storage]

[0104] After charging at a constant current of 0.1C until the closed circuit voltage of the battery reaches 2.75V, the battery is stored at 25°C for 72 hours. After storage, the battery is discharged at a constant current of 0.1C until the closed circuit voltage of the battery reaches 1.45V. The change in the discharge capacity of the battery at this time is calculated as the capacity residual rate (%), and the change in the open circuit voltage of the battery during charging and storage (V) is also calculated. That is,

[0105] Capacity retention rate (%)=(discharge capacity during charge storage test) / (discharge capacity before charge storage test)×100.

[0106] The charge storage test was performed in an environment of 25° C. The capacity retention rate and the change in open circuit voltage (V) were used as evaluations of stability during charge storage.

[0107] Table 1 shows the evaluation results.

[0108] [Table 1]

[0109]

[0110] The higher the residual capacity rate is and the smaller the change in open circuit voltage is, the more stable the battery is.

[0111] As shown in Table 1, the secondary battery of Example 1 can suppress the decrease in the residual capacity rate and voltage during charge storage compared to the secondary battery of Comparative Example 1. That is, the charge storage stability of the secondary battery of Example 1 is improved.

[0112] In addition, the negative electrode of the manufactured battery is lithium titanate, which is a material with almost no potential change at the negative electrode. Thus, suppressing the open circuit voltage reduction means suppressing the potential reduction of the positive electrode. Therefore, it can be known that by covering the positive electrode active material with W oxide, the potential reduction of the positive electrode is suppressed, and the charging storage stability of the battery can be improved. This is because: the oxygen-induced overvoltage of water is increased by the presence of W oxide on the surface of the lithium transition metal oxide, which suppresses the oxidative decomposition reaction of the aqueous electrolyte occurring on the surface of the positive electrode active material and the pH increase of the electrolyte and the dissolution of the transition metal associated therewith. Thus, it can be considered that a high discharge capacity and voltage can be maintained even after the charging storage test.

[0113] It should be noted that the types of oxides present on the surface of the lithium transition metal oxide show the same effect even if they are other than W oxides. This is because, for example, by making oxides of B, Si, P, Ti, V, Mn, Al, Mg, Ca, Zr, W, Nb, Ta, In, Mo and Sn, which are stably present in the charge and discharge reaction of the secondary battery, present on the surface of the positive electrode active material, the oxygen overvoltage of water is increased without adversely affecting the positive reaction of the secondary battery.

[0114] Description of Reference Numerals

[0115] 10. Positive electrode active material

[0116] 14 Primary particles

[0117] 16 Secondary particles.

Claims

1. A secondary battery comprising: A positive electrode containing a positive electrode active material for a secondary battery; a negative electrode comprising a negative electrode active material; and An electrolyte made by dissolving lithium salt in water. The positive electrode active material comprises a general formula Li x M 1-y L y A lithium transition metal oxide represented by O2, wherein 0.9≤x≤1.1, 0≤y<0.6; element M is at least one selected from the group consisting of Ni and Co; element L is Al, The positive electrode active material is a composite oxide having an oxide of W on the surface of the lithium transition metal oxide. The composite oxide includes primary particles and secondary particles formed by aggregation of the primary particles. The W oxide is present on the surface of the primary particles and the surface layer of the secondary particles. The molar ratio of water in the electrolyte to 1 mol of lithium salt is less than 4 mol, The amount of the element W is 0.1 mol% or more and 2 mol% or less relative to the lithium transition metal oxide.

2. The secondary battery according to claim 1, wherein The x in the general formula is 0.95 <x<1.02。 3. The secondary battery according to claim 1, wherein The pH of the electrolyte is greater than 10.

Citation Information

Patent Citations

  • Water system secondary battery

    CN107403968A

  • Electrolyte particle, cathode, anode and lithium secondary battery

    JP2005243342A

  • Lithium secondary battery and method for manufacturing the same

    JP2011238461A

  • Lithium ion secondary battery

    US20070141470A1

  • Positive electrode for lithium secondary battery, and lithium secondary battery employing the same

    US20130130113A1